Evidence of a correlation between magnetic and structural transitions in Y2−xZnxRu2O7 pyrochlore compounds. Issue 122 (24th November 2015) - Berti, Giulia; Sanna, Samuele; Ruiz-Bustos, Rocío; van Duijn, Joost; Brambilla, Alberto; Muñoz-Noval, Álvaro; Demartin, Francesco; Duò, Lamberto; Castellano, Carlo
Abstract : Strong magnetoelastic coupling and local order–disorder transition at T * > T N observed up to x = 0.10 in Y2− x Zn x Ru2 O7 pyrochlores. Abstract : We report on an experimental investigation of the magnetic and structural properties of the Y2− x Zn x Ru2 O7 pyrochlore system as a function of the Zn doping in the range 0.00 ≤ x ≤ 0.20. Magnetization and muon spin relaxation measurements show that the antiferromagnetic transition typical of the undoped compound at T N = 77 K is slightly reduced and broadened in the Zn doped sample. Extended X-ray absorption fine structure measurements show a peak in the Ru–O(1) first shell Debye–Waller factor at a temperature T DW ≈ T N, giving evidence for a strong magnetoelastic coupling detected up to x = 0.10. A local precursor order–disorder transition at T * > T N is also observed up to x = 0.10. For x > 0.10 these local structural features are hidden due to the increasing local lattice distortion induced by the Zn 2+ dopant whereas the magnetic transition is still present.